Evaluation of Yunus Emre Poems Designed as Digital Poetry with Web 2.0 Tools in Terms of Language and Values Education - Neslihan Karakuş; Kübra Özçetin; Mehmet Önder Karacaoğlu (Sakarya University Journal of Education)
This study aims to assess the contribution of digital poems by Yunus Emre—a prominent figure in Turkish-Islamic culture—created using Web 2.0 tools to language and values education from the perspective of teachers. Within the scope of the research, eight poems from Yunus Emre’s Divan, selected based on their appropriateness for students' age and developmental levels, were transformed into digital poems using Canva. Skill-based Turkish language questions were appended to the end of these poems, supported by activities focused on fundamental language skills, thereby converting them into unique, technology-enhanced teaching tools.The prepared digital poems were assessed by 17 Turkish language teachers working in public secondary schools in Manisa. The teachers provided insights into the effects of digital poems on basic language skills, life perspectives, values education, friend selection, cultural development, and assessment methods. Additionally, their metaphorical perceptions of the concepts of "digital poetry" and "Yunus Emre" were examined.Teachers' feedback was collected through a survey developed by the researchers and administered via Google Survey. The research data were analyzed using content analysis. The findings indicate that the seven poems, centered around themes of love and brotherhood in Yunus Emre’s Divan, contribute positively to students' fundamental language skills, perspectives on life, values education, friend selection, and cultural development. The importance of introducing such literary works to students was emphasized. Furthermore, it was concluded that the content, developed based on insights from subject matter experts and teachers, could serve as valuable instructional materials in Turkish language education.